Strategi Pendayagunaan Program “Gresik Berdaya” dalam Meningkatkan Ekonomi Mustahik di Badan Amil Zakat Nasional (BAZNAS) Gresik - Taufiqur Rahman (STAI Nurul Islam Mojokerto, 2025)
In this increasingly developing era, poverty is still a problem in every country, therefore there is a need for policies to reduce poverty, one of which is through zakat. Where one of the institutions that play a role in the utilization of zakat funds, namely the Gresik Regency National Amil Zakat Agency (BAZNAS) has the duties and functions of collecting and distributing, utilizing zakat, infaq, and alms (ZIS) which has several programs in utilizing ZIS funds, one of which is the Gresik Berdaya program which consists of 3 programs namely work tool assistance, business capital assistance or microfinance and rolling livestock assistance which aims to improve the mustahik economy.The type of research used by researchers in this study is a type of qualitative research with a qualitative descriptive approach that uses field research through observation, interviews and documentation of the head of the distribution department, the distribution staff and the mustahik who receive assistance. The results showed that there were 3 assistance strategies for the utilization of the Gresik Empowered program, including work tool assistance, business capital assistance, and rolling livestock assistance. BAZNAS Gresik Regency implemented a strategy by carefully selecting mustahik so that the assistance provided was truly beneficial to the mustahik, and also working with the village UPZ the assistance can be felt by the BAZNAS Gresik mustahik